Full Spine X-Ray Examination: Experience Outcome - Sergio Palandri (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
The aim of this work is to provide a simple and detailed protocol to perform full spine X-ray examination in diagnosis and follow-up of AIS, direcrtly relevant in practice. Ionizing radiations, even at low doses, present side effects that are well known as girls and young women constitute the most sensible individuals from X-ray protection point of view. On the other side full spine radiography is the gold standard in diagnosis and follow-up of AIS, where individuals involved are typically girls and young women. For these reasons, a specific care performing X-ray examination in this scope, is mandatory. Our protocol rises from 8y experience in application and study of the scoliosis in the first two decades of life, combining the orthopaedist’s requirements and the surgical requirements together with the care to the specific category made up the majority individuals involved, which require a particularly significant relational feature. For a better usability and clarity, we considered three main topics: a) single examination b) examination during orthotic treatment and c) pre-op control. For each one we explained number and type of X-ray view used and how we performed them with the assistance of detailed figures. By comparing X-ray images before and after the application of our protocol, we saw a significant increase in the quality of the produced images as well as a positive feedback from patients and parents acceptance. An extended collaboration between the Orthopaedic Surgeon and the Radiographer, has led to a clear improvement in technical execution and in an exposure dose reduction. Furthermore a particular attention to the patient’s comfort, along with some technical stratagems, led to an improving effectiveness of the services supplied.